(untitled) (REVISTA SAYWA, 2024)
Abstract The purpose of the present study was to standardize a fast and effortless methodology for the detection of SARS-CoV-2, by reverse transcription loop-mediated isothermal nucleic acid amplification technique (RT-LAMP) for COVID-19 diagnosis. Standardization was made in RNA samples previously confirmed by RT-qPCR using the Charité/Berlin protocol. We detail the steps of the technique and highlight use of S-123 primers. In conclusion, RT-LAMP with S-123 primers for SARS-CoV-2 in RNA samples, shows a high level of performance compared with gold standard technique RT-qPCR.